Dynamic Change of Mangroves in Aceh Tamiang Regency using Landsat Temporal Data, 2000 to 2023 - Marfi, Khairani Putri; Asy'Ari, Rahmat; Azelia Dwi Rahmawati; Ali Dzulfigar; Aulia Ulfa; Puspitasari, Raditya Febri; Yudi Setiawan; Neviaty P Zamani; Rahmat Pramulya (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Mangroves, known for their high productivity, play vital roles in physical, ecological, and economic aspects that benefit human life. However, these ecosystems are currently threatened by climate change and human activities. To address this challenge, Indonesia aims to rehabilitate 600,000 hectares of mangroves by 2024. Effectively monitoring changes in mangrove dynamics is crucial for achieving this goal. This study focuses on understanding the dynamic change of the mangrove land cover in Aceh Tamiang from 2000 to 2023. Mangrove dynamics in Aceh Tamiang are important because it has the largest mangrove area in East Aceh, which is decreasing due to conversion to the oil palm industry. The classification using random forest (RF) algorithm by utilizing VWB-IC (Vegetation-Water-Built-up Index Combined), which area NDVI, SAVI, ARVI, GNDVI, SLAVI, and EVI as vegetation indices; MNDWI and ANDWI as water indices; and NDBI as built-up index. The employment of this combination is necessary to enhance the accuracy of classification due to the addition of more input parameters to machine learning. The image data are acquired through Landsat 5 for 2000 and 8 and 9 satellites for 2023. The observed dynamics include mangroves transitioning into fishponds (768 ha) and plantations (2,679 ha) between 2000 and 2023. The processed data indicates a decrease in the Aceh Tamiaang mangrove area from 13,270 ha in 2000 to 9,386 ha in 2023. These results can be used to determine mangrove rehabilitation policies in Aceh Tamiang, Indonesia.